E-BOOK: PENGEMBANGAN MATERI AJAR KOHERENSI ANTARGAGASAN PADA MENULIS TEKS BIOGRAFI BERBASIS PENDEKATAN PEDAGOGI GENRE - Dwi Nur Apriliani; Sintowati Rini Utami; Etsa Purbarani (Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study was motivated by the identification of issues and the need for teaching materials on coherent writing. The study aims to develop teaching materials on coherence between ideas in writing biographical texts for 10th-grade students based on a genre-based pedagogical approach. This study falls under the category of Research and Development (R&D) using the ADDIE model (analysis, design, development, implementation, and evaluation), which was adapted to include analysis, design, and development. The data collected consisted of observation results and a needs analysis questionnaire. Data analysis was conducted using both quantitative and qualitative methods. The result of this study is teaching materials on coherence between ideas in writing 10th-grade biographical texts based on a genre pedagogy approach. The quality of the teaching materials on coherence between ideas in writing biographical texts received a rating of 97.8% from subject matter experts and 98.75% from learning methodology experts, with a rating category of “very good/highly suitable.” This study produced teaching materials that can serve as an additional resource for training students' writing skills in creating coherent texts.